JARE-35 GLACIOLOGICAL ACTIVITY AT DOME FUJI STATION, ANTARCTICA - ショウジ, ヒトシ; サイトウ, タカシ; サイトウ, タケシ; シライワ, タカユキ; タグチ, ユウジ; ヨコヤマ, コタロウ; ホンドウ, タケオ; ワタナベ, オキツグ; モトヤマ, ヒデアキ; フルカワ, テルオ; タケカワ, モトアキ; アゲタ, ユタカ; et al. (National Institute of Polar Research, 1996)
P(論文) Information on paleoenvironmental changes on the earth is preserved in the form of physical and chemical stratigraphic features in large polar ice sheets. Extraction of ice core signals makes it possible to evaluate and reconstruct past global variations of climate and stmospheric circulation. A deep ice coring and analysis effort was started at Dome Fuji Station (77°19′01″S, 39°42′12″E). Antarctica by the 32nd Japanese Antarctic Research Expedition (JARE-32) in 1991 and will be completed with continuous deep core retrieval in 1997. JARE-32,-33 and -34 parties set up a traverse route from Syowa Station to Dome Fuji Station, selected the coring site considering the results from radar soundings and GPS positions, and conducted shallow ice coring to a depth of 112.6m at the site. JARE-35 party completed construction of a camping/drilling facility for JARE-36 and -37 wintering parties to perform deep ice coring through the ice sheet with a thickness of approximately 3km. JARE-36 parties also conducted glaciological, meteorological and medical observations during the periods of cargo transportation and camp-construction activities both along the traverse route and at the Dome Fuji Station drilling site. departmental bulletin paper